Préserver et mettre en valeur l'histoire et le patrimoine de l'immigration dans un musée d'histoire: l'expérience du Centre d'histoire de Montréal - Leclerc, Jean-François (Musées, histoire, migrations, 2015)
Keywords: Centre d'histoire de Montréal; Histoire; Musées

L’université et le musée: une cohabitation difficile - Young, Brian (Les musées en mouvement: nouvelles conceptions, nouveaux publics (Belgique, Canada), 2000)
Keywords: Musées

Le McCord: l'histoire d'un musée universitaire, 1921-1996 - Young, Brian (Hurtubise HMH, 2001)
Translators: _:n11207
Keywords: Musée McCord; Musées

Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
issued: 2005/2006
Keywords: Archives; Musée McCord; Musées

L'historien, le musée et la diffusion de l'histoire - Burgess, Joanne (Revue d'histoire de l'Amérique française, 2003)
issued: 2003-22-00
Keywords: Histoire; Musées

La relation entre les agents d'éducation scolaire et les agents d'éducation muséale dans le cadre d'une collaboration entre le musée et l'école - Vadeboncoeur, Guy (Université du Québec à Montréal, 2003)
Keywords: Musées

Le musée de l’Institut canadien de Montréal (1852-1882), un projet inachevé - Lacroix, Laurier (Les Cahiers des dix, 2010)
Number: 64
Keywords: Institut canadien; Musées

Le rôle de la médiation culturelle dans la perception de l'art chez les adolescents: étude de cas au Musée d'art contemporain de Montréal - Bonnardot, Delphine (Université du Québec à Montréal, 2003)
Keywords: Musée d’art contemporain de Montréal; Musées

Les musées d'histoire et l'histoire du Vieux-Montréal: des enjeux et des perspectives - Dufresne, Sylvie (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Musées; Quartiers; Vieux-Montréal

Le Musée de l'École des HÉC (1910-1956) - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2001)
issued: 2001-21-00
Keywords: Expositions; Musées; École des hautes études commerciales

Comment être un musée de ville au service des citoyens? Un parcours et quelques pistes d'action - Leclerc, Jean-François (Museos y parques naturales: comunidades locales, administraciones publicas y patrimonializacion de la cultura y la naturaleza, 2010)
Keywords: Centre d'histoire de Montréal; Histoire; Musées

Le Japon contenu: La naissance des collections asiatiques au Musée des beaux-arts de Montréal - Vigo, Laura (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Le temps d'une leçon: l'utilisation et le rôle des musées scolaires dans les écoles de filles entre 1860 et 1970 au Québec - Thiboutot, France (Le patrimoine des communautés religieuses. Empreintes et approches, 2018)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Musées; Patrimoine; Villa-Maria

L’Écomusée du fier monde de Montréal: histoires, patrimoines et espaces urbains - Burgess, Joanne (Les musées en mouvement: nouvelles conceptions, nouveaux publics (Belgique, Canada), 2000)
Keywords: Histoire; Musées; Patrimoine; Écomusée du fier monde

La patrimonialisation de l'environnement au Biodôme de Montréal - Crenn, Gaëlle (Culture & Musées, 2003)
Number: 1
Keywords: Patrimoine

Cliquer sur l’histoire - Larouche, Marie-Claude (Continuité, 2004)
issued: 2004-24-00/2005-24-00
Keywords: Musée McCord; Musées

Suspended conversations: the afterlife of memory in photographic albums - Langford, Martha (McGill-Queen's University Press, 2008)
Keywords: Musée McCord; Musées; Photographie

Restaurateur en milieu muséal: mission prévention - Bédard, Rodrigue (Continuité, 2003)
issued: 2003-24-00/2004-24-00
Keywords: Musées; Restaurant

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

''Run'' de lait: le laitier et la bouteille - Giroux, Éric (Gastronomie québécoise et patrimoine, 2013)
Keywords: Lait; Musées

Témoignages autochtones - McCaffrey, Maria T. (Continuité, 2002)
issued: 2002-21-00
Keywords: Autochtones; Expositions; Musée McCord; Musées

First Nations, Museums and McCord Museum's Journey Across Borders - Jarosova, Marketa (Université Concordia, 2001)
Keywords: Autochtones; Expositions; Musée McCord; Musées

La collection muséale d'art contemporain aux limites du pluralisme et du syncrétisme identitaire - Lévesque, France (Université du Québec à Montréal, 2003)
Keywords: Musée d’art contemporain de Montréal; Musées

Pointe-à-Callière: le marché, façon XVIIIe - Labrosse, Francine (Continuité, 2003)
issued: 2003-23-00
Keywords: Marchés; Musée Pointe-à-Callière; Musées

Visions of Canada: Photographs and History in a Museum, 1921-1967 - McNabb, Heather (Université Concordia, 2015)
Keywords: Histoire; Musée McCord; Musées; Photographie

Pointe-à-Callière et la muséologie québécoise - Montpetit, Raymond (Montréal en tête, 2020)
issued: 2020-24-00
Keywords: Archéologie; Musée Pointe-à-Callière; Musées

Pointe-à-Callière: the making of a museum - Lelièvre, Francine (2023)
OCLC: 1380348579
Keywords: Musée Pointe-à-Callière

Les défis et enjeux du changement vers le développement durable: l'analyse stratégique des muséums nature de Montréal - Procéda, Aude (Université du Québec à Montréal, 2007)
Keywords: Jardin botanique; Musées

Pointe-à-Callière, lieu de fondation de Montréal - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Keywords: Musée Pointe-à-Callière; Musées; Pointe-à-Callière

Pointe-à-Callière, birthplace of Montréal - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Translators: _:n57527
Keywords: Musée Pointe-à-Callière; Musées; Pointe-à-Callière

An Analysis of the Task Force on Museums and First Peoples: The Changing Representation of Aboriginal Histories in Museums - Bolton, Stephanie (Université Concordia, 2004)
Keywords: Autochtones; Histoire; Musées

The Making and Unmaking of a University Museum: the McCord, 1921-1996 - Young, Brian J. (McGill-Queen's University Press, 2000)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Location, Location, Location: David Ross McCord and the Makings of Canadian History - Harvey, Katryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Number: 1
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
issued: 2008/2009
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Le bain généreux de l’Écomusée du fier monde - de Roquefeuille, Margot (Conserveries mémorielles, 2016)
Number: 19
Keywords: Musées; Patrimoine; Écomusée du fier monde

Le Centre d'histoire de Montréal: le passé mis au jour - Leclerc, Jean-François (Cap-aux-Diamants, 2002)
issued: 20021-21-00
Keywords: Centre d'histoire de Montréal; Histoire; Musées

Études de cas - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La "vie sociale" de la collection de céramiques japonaises de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The “Social Life” of the Van Horne Japanese Ceramic Collection - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Ceramics Catalogue - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Case Studies - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The Nation Builder - Newman, Peter C. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Obsession: Sir William Van Horne's Japanese Ceramics - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Le bâtisseur de nation - Newman, Peter C. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne and Friends: Collecting European Art in Montreal’s Square Mile - Brooke, Janet M. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Obsession: Les céramiques japonaises de Sir William Van Horne - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Japan Contained: The Birth of the Asian Collections at the Montreal Museum of Fine Arts - Vigo, Laura (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne’s Notebooks - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Les carnets de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne et ses amis: Collectionner l’art européen dans le Mille carré de Montréal - Brooke, Janet M. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Catalogue des céramiques - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Confitures et marinades Raymond: faites pour plaire! - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
issued: 2016-21-00
Keywords: Alimentation; Expositions; Musées; Écomusée du fier monde

Les sources orales au coeur de l'exposition muséale. L'expérience du Centre d'histoire de Montréal - Charlebois, Catherine; Leclerc, Jean-François (Revue d'histoire de l'Amérique française, 2015)
issued: 2015-22-00/2015-23-00
Keywords: Centre d'histoire de Montréal; Expositions; Histoire; Musées

Gardiens de l’histoire - Giroux, Éric; Charbonneau, Réjean (Continuité, 2011)
issued: 2011-23-00
Keywords: Atelier d'histoire d'Hochelaga-Maisonneuve; Histoire; Musées; Écomusée du fier monde

Au temps de la fondation de Montréal, Pointe-à-Callière - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Keywords: Archéologie; Autochtones; Callière; Louis-Hector de; Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Mance; Jeanne; Musée Pointe-à-Callière; Musées; Pointe-à-Callière

When Montréal was founded, Pointe-à-Callière - Poussart, Annick (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2017)
Translators: _:n55282 Translators: _:n56459
Keywords: Archéologie; Autochtones; Callière; Louis-Hector de; Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Mance; Jeanne; Musée Pointe-à-Callière; Musées; Pointe-à-Callière

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Number: 2
Keywords: Abbott; Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

Le carnet de bal. Objet précieux et capricieux pour l'histoire de la danse récréative à Montréal entre 1870 et 1940 - Roquigny, Peggy (À la recherche du savoir: Nouveaux échanges sur les collections du Musée McCord / Collecting Knowledge: New Dialogues on McCord Museum, 2016)
Keywords: Danse

Collectionner à Montréal au 19e siècle: Gerald E. Hart et la construction d'une pratique utile - Truchon, Caroline (À la recherche du savoir: Nouveaux échanges sur les collections du Musée McCord / Collecting Knowledge: New Dialogues on McCord Museum, 2016)
Keywords: Numismatie

Deux quotidiens se rencontrent. Le regard de l'historien - Burgess, Joanne; Lauzon, Gilles (Exposition virtuelle: Deux quotidiens se rencontrent, 2002)
Keywords: Notman; William; Photographie